2015
DOI: 10.1159/000430165
|View full text |Cite
|
Sign up to set email alerts
|

Ultra Low Dose Delta 9-Tetrahydrocannabinol Protects Mouse Liver from Ischemia Reperfusion Injury

Abstract: Background/Aims: Ischemia/reperfusion (I/R) injury is the main cause of both primary graft dysfunction and primary non-function of liver allografts. Cannabinoids has been reported to attenuate myocardial, cerebral and hepatic I/R oxidative injury. Delta-9-tetrahydrocannabinol (THC), a cannabinoid agonist, is the active components of marijuana. In this study we examined the role of ultralow dose THC (0.002mg/kg) in the protection of livers from I/R injury. This extremely low dose of THC was previously found by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…The major cannabinoid component, delta-9-tetrahydrocannabinol (Δ 9 -THC, often referred to just as THC), is primarily responsible for the psychoactive effects of marijuana [3]. THC also produces a variety of negative effects including tachycardia and impairment of memory and motor function [4]. These effects of THC are mainly mediated by binding to CB1R (cannabinoid receptor 1, brain-type) [5] and CB2R (cannabinoid receptor 2, spleen-type) [6], two major cannabinoid receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The major cannabinoid component, delta-9-tetrahydrocannabinol (Δ 9 -THC, often referred to just as THC), is primarily responsible for the psychoactive effects of marijuana [3]. THC also produces a variety of negative effects including tachycardia and impairment of memory and motor function [4]. These effects of THC are mainly mediated by binding to CB1R (cannabinoid receptor 1, brain-type) [5] and CB2R (cannabinoid receptor 2, spleen-type) [6], two major cannabinoid receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue injury as a result of initial hypoxic insult is enhanced and accelerated by the shear stress of sudden blood supply that disrupts the normal homeostatic mechanisms and results in generation of free radicals [3]. Increase in reactive oxygen species (ROS) have been shown to trigger a series of molecular events which involve activation of hepatic Kupffer cells, secretion of inflammatory cytokines, chemotactic factors, and recruitment of neutrophils and macrophages, all of which contribute to hepatocellular damage and death [4][5][6]. Previous studies have shown that Kupffer cells and neutrophils in IR injury release TNF-α, IL-1β and IL-6 which activate c-Jun N-terminal kinase 2-thereby resulting in disruption of mitochondrial membrane permeability with subsequent cytochrome c release and caspase mediated apoptotic hepatocyte death [7].…”
Section: Introductionmentioning
confidence: 99%
“…The CB 2 receptors were initially identified in the immune system [18]. Immunomodulatory property of cannabinoids via the CB 2 receptor has later been discovered, which fuelled investigations of CB 2 receptor agonists as potential therapeutic candidates for autoimmune diseases and ischaemic organ injuries [19][20][21][22]. Thus, administration of delta-9-tetrahydrocannabinol, a derivative of cannabinoid, significantly inhibited atherosclerosis progression in mice [23].…”
Section: Introductionmentioning
confidence: 99%